ANALISIS KEBIJAKAN SISTEM PEMUNGUTAN PAJAK REKLAME DI KOTA TOMOHON ( Studi Pada Dinas Pendapatan, Pengelolaan Keuangan dan Asset Kota Tomohon ) - Sualang, Christo A.; Ilat, Ventje; Wangkar, Anneke (Universitas Sam Ratulangi, 2016)
Advertisising tax collection system is essential in supporting the implementation of billboards orderly and neat and can create and atmosphere conducive bussines climate, public tranquility and public order can be realized. Therefore, if the better the organization and arrangement of adversement in the district/region, then the optimal well as local revenue from the tax sector. The purpose of this study was to determine policy adverstising tax collection system in the city tomohon and to determine obstacles in the collection of adversticement tax in tomohon. The data used in this research is secondary data is yhe data coming from the department of refenue, finance and asset management tomohon. The result showed that the adversment taxation system policy has not completely go according to the legislation in force. Planning policy and adversment tax voting system includes how the arrangement regarding the implementation, licensing, system and incidental arrangement permanent billboard, rental values and tax rates billboard, as well as system and procedures adverstisement taxation. Advertisement taxation obstacles in tomohon, among others: implementation of billboards not in accordance with the applicable local regulations and constraints in terms of licensing advertisement.